The Hegemony of Capitalism in the 2024 Indonesia General Election - Ekayanta, Fredick Broven (Talenta Publisher, 2024)
This article explains how the operation of hegemonic power of capitalism works in the 2024 election in Indonesia, both in the presidential and legislative elections. The hegemonic power refers to the third-dimensional power introduced by Lukes, namely power in the ideological realm. This article argues that capitalism hegemony â€œgraspsâ€ all dominant narratives that emerged during the 2024 elections, both from election participants and civil societies. By using the concept of ideological cynicism introduced by Å½iÅ¾ek, this article explains that capitalism in the ideological realm can be so effective because it appears not as an ideology, but as a kind of truth believed by everyone.